How to Coach Individuals, Teams, and Organizations to Master Transformational Change - Hacker, Stephen K (Business Expert Press, 2012)
Ebook from IG Library ; The book's unique contributions to the field of individual and collective transformation in the workplace are built on three central ideas: Radical improvement is possible only through a transformation rooted in expanding consciousness and integrating the body, mind, and spirit. Purpose and vision can then be drawn from deeper wisdom and fueled from a larger source of creative energy, spirit-generated creativity. Radical improvement in collective performance is not a top-down phenomenon. Rather it hinges upon the individual members embracing transformation in their own lives and finding alignment between their and the group's purpose, vision, and values Radical improvement can be implemented, sustained, and repeated if it is pursued through a holistic, systematic, yet practical framework that also incorporates solid processes for planning and implementing change and measuring results.